1991
DOI: 10.1136/sti.67.6.464
|View full text |Cite
|
Sign up to set email alerts
|

Anal intercourse: a risk factor for anal papillomavirus infection in women?

Abstract: Objective-To determine whether anal intercourse is a risk factor for anal HPV infection in women.Design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…The results of this study were similar to those of other studies that have not found any association between anal HPV infection and anal intercourse [Law et al, 1991; Moscicki et al, 2003], which may suggest alternative transmission routes, including sexual and nonsexual routes [Winer et al, 2003]. The trauma associated with anal intercourse is a risk factor for the cytological abnormalities caused by the virus.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study were similar to those of other studies that have not found any association between anal HPV infection and anal intercourse [Law et al, 1991; Moscicki et al, 2003], which may suggest alternative transmission routes, including sexual and nonsexual routes [Winer et al, 2003]. The trauma associated with anal intercourse is a risk factor for the cytological abnormalities caused by the virus.…”
Section: Discussionsupporting
confidence: 90%
“…Hosseini et al, (2018) showed that the patients who had anal intercourse showed more positive anal cytology than those who did not significantly. However some studied reported no association between anal intercourse and the presence of anal HPV infection (Law et al, 1991). In our study, case of AIN 3 had never had anal intercourse.…”
Section: Discussioncontrasting
confidence: 53%
“…Information related to other risk factors, such as race/ethnicity, sexual activity/history, and socio-economic status were not available for study [8]. Research has shown that certain types of sexual behavior increase the risk of genital HPV infection and anal cancer, such as having sex at an early age, having multiple sexual partners, sexual orientation, and participating in receptive anal intercourse [8,27].…”
Section: Discussionmentioning
confidence: 99%